PENGARUH TANAH MINERAL DAN ABU JANJANG KELAPA SAWIT PADA MEDIUM GAMBUT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Suprianto '; Wawan '; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aimed to determine the effect of mineral soil and oil palm bunch ash on peat medium on the growth of oil palm seedling (Elaeis guineensis Jacq.) in main nursery. The research was conducted from April to August 2015. This research is a 4 x 4 factorial experiment arranged in a completely randomized design (CRD). The first factor is effect mineral soil consist of four levels: 0, 50, 75 and 100 g/5,6 kg peat soil. The second factor is effect oil palm bunch ash consist of four levels: 0, 25, 50 and 75 g/5,6 kg peat soil, thus there are 16 combinations of treatment is repeated three times, so there are 48 experimental units. Data were analyzed using ANOVA and continued with further test Duncan’s New Multiple Range Test (DNMRT) at 5%. The results showed that the combination of mineral soil 10 ton/ha with oil palm bunch ash 15 ton/ha increase height and seedling dry weight. Giving oil palm bunch ash increase hight and tends to increase the volume of roots, dry weight and ratio root crown. Giving mineral soil up to 15 ton/ha tends to increase the volume of roots, dry weight and ratio root crown. Keywords: Mineral soil, peat soil, oil palm bunch ash, main nursery